Bioconcentration of cedarwood oil constituents in rainbow trout. Issue 5 (16th March 2021) - Sühring, Roxana; Chen, Chang-Er; McLachlan, Michael S.; MacLeod, Matthew
Abstract : Bioconcentration of individual cedarwood oil constituents tested using an abbreviated dietary exposure in vivo test with internal benchmarking. Abstract : Cedarwood oil is an essential oil used as a fragrance material and insect repellent. Its main constituents are sesquiterpenes which are potentially bioaccumulative according to the REACH screening criteria. Cedarwood oil is a complex mixture of hydrophobic and volatile organic chemicals. The volatility and limited water solubility of its constituents are a challenge for standard bioconcentration factor (BCF) test methods using aqueous exposure. We used an abbreviated dietary exposure in vivo testing protocol with internal benchmark substances as "internal standards" to derive the BCF of cedarwood oil constituents using rainbow trout ( Oncorhynchus mykiss ). Internal benchmarking proved to be a useful tool to control for inter-individual variability, enabling us to calculate the BCF for all major cedarwood oil constituents as a mixture. We found that the BCF of two out of six analysed cedarwood oil constituents exceed a BCF of 5000 and two others exceed a BCF of 2000 (90% confidence level) even though we found evidence for biotransformation for individual constituents. The results of this study indicate that more work is warranted to study the bioaccumulation of essential oils and highlights the utility of internal benchmarking in in vivo dietary exposure BCF tests to increase robustness and allow for the BCF measurement of complex mixtures.